Building condition assessment on ceiling at management office and private higher education institution, Kota Damansara,Selangor Darul Ehsan / Mohd Ashraf Iskandar Mohd Jaya - Mohd Jaya, Mohd Ashraf Iskandar (2015)
AMAS FM Consultant Sdn Bhd (AFC) was appointed by 'Pertubuhan Peladang Kebangsaan' (NAFAS) to carry out Building Condition Assessment. The work involved is to record the defects including type of defects and the amount of defects, provide repair recommendations, cause defects, overall condition and estimated cost to repair. From the survey that has been carried out, 26 defect of 186 needs minor service.131 defect of 186 need minor repair,28 defect needs major repair or replacement while 1 defect needs immediately action. For the priority, 139 defect need to repair as in plan maintenance and 47 defect need routine priority in maintenance. Based on scale, for scale 2 defect as much as 26 (14%).131 defect on the scale 3 (70%) and scale 4 is 28 defect (15%).Next, scale 5 is 1 (1%).